2021
DOI: 10.1177/0954405420986083
|View full text |Cite
|
Sign up to set email alerts
|

Thermal modelling of cutting tool temperatures and heat partition in orthogonal machining of high-strength alloy steel

Abstract: Cutting temperatures and heat partition into the cutting tool are critical factors that significantly affect tool life and part accuracy during metal removal operations, especially in dry machining. Among many thermal modelling studies, uniform heat partition ratio, and/or uniform heat intensity along the tool-chip interface are frequently assumed. This assumption is not valid in actual machining and can lead to erroneous estimated results in the presence of sticking and sliding friction zones. Therefore, it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…It is confirmed that the higher cutting speed leads to an elevated cutting temperature. 48 Under this circumstance, tensile residual stress is more intended to generate within the machined surface layer due to thermal expansion. After all, fatigue crack is more prone to initiate from the machined surface, 49 especially if the generated residual stress is in a tensile state, which thus causes a significantly decreasing fracture toughness.…”
Section: Resultsmentioning
confidence: 99%
“…It is confirmed that the higher cutting speed leads to an elevated cutting temperature. 48 Under this circumstance, tensile residual stress is more intended to generate within the machined surface layer due to thermal expansion. After all, fatigue crack is more prone to initiate from the machined surface, 49 especially if the generated residual stress is in a tensile state, which thus causes a significantly decreasing fracture toughness.…”
Section: Resultsmentioning
confidence: 99%
“…The contact areas of the rubbing surfaces of the tool, chips, and workpiece being processed are small, and the pressure and friction rate exerted on them are extremely high. The high temperature in the cutting zone is the cause of structural changes in the material of the cutting tool and the reason for the rapid loss of its performance [88][89][90]. Therefore, to explain the physical nature of the increase in the tool material durability, it is crucial to study the changes in temperature fields in the cutting wedge of the tool during operation.…”
Section: Quantitative Assessment Of the Cutting Part Wear And Roughnessmentioning
confidence: 99%
“…Metal machining creates substantial thermal and mechanical loads that can impact the mechanical behaviours of both tools and workpieces [1][2][3][4][5][6][7]. However, the machining industry focuses more on the mechanical loads of the operations.…”
Section: Introductionmentioning
confidence: 99%